Application of Therapeutic Communication Techniques Improves Self-Control in Patients With Violent Behavior - Adriana Della Putri Hartono; Rusminah Rusminah; Siswanto Siswanto; Ida Rianawaty (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Background: Schizophrenia is a mental disorder characterized by the sufferer's difficulty in distinguishing reality from fantasy. Schizophrenia includes several symptoms such as violent behavior, hallucinations, delusions, social isolation and low self-esteem. Violent behavior if not treated can cause harm to the sufferer himself, others, and the surrounding environment to disrupt the quality of life of the sufferer. Objective: To determine the application of therapeutic communication techniques in patients with violent behavior in Mr. Z and Mr. T who experience the main problem of violent behavior in schizophrenia patients. Method: This study is a qualitative descriptive study with a case study approach, using 2 respondents, namely patients who experienced violent behavior in the Lily 13 Room of the Ministry of Health, Soerojo Hospital, Magelang City. The application was carried out for 4 consecutive days with an application time of 30 minutes, observing signs and symptoms of self-care deficits before and after the application of the action. Results: Therapeutic Communication Techniques can reduce signs and symptoms of violent behavior through the results of observations of signs and symptoms of violent behavior in schizophrenia patients relatively decreasing. Conclusion: The application of therapeutic communication techniques in increasing self-control in schizophrenia patients.